(untitled) (Sebha University Conference Proceedings, 2025)
This paper discusses the mechanical and durability properties of concrete with sawdust as a partial substitute of fine aggregate. Sawdust obtained at a wood workshop in Karbala was used as a replacement in concrete mixes of 0%, 5%, 10%, and 15%. The experimental program tested compressive strength, splitting tensile strength, and density at the age of 7 and 28 days of curing. It was found that 5% replacement of sawdust increased the compressive and tensile strength slightly relative to the control mix, whereas replacement levels of more than 5 % causes a progressive decrease in strength and density. These decreases are owed to the high porosity and low density due to the fibrous and lightweight nature of sawdust. However, a 10% replacement sustained favourable mechanical performance and offered economic and environmental benefits. The results indicate the viability of using small amounts of sawdust as a substitute of the conventional sand in concrete. The research proposes more research on mix design optimization and long-term performance of sawdust concrete in different environment conditions.